PENGARUH PERCEIVED QUALITY DAN BRAND IMAGE TERHADAP BRAND TRUST PRODUK KOSMETIK WARDAH - Izzati, Rosyida Rahma (Jurnal Ilmu Manajemen, 2019)
The purpose of this research is to analyze: 1) influence of perceived quality on brand trust and 2) influence brand image on brand trust. Data was collected from 105 respondent who are consumer of Wardah cosmetics in Surakarta and the surrounding area. The method of analysis use multiple linear regression. Based on the test of all instrument variables are valid and reliable. Classical assumption test indicate that the data normally distribute and linier, moreover there are no multicollinearity and heteroschedastisity. The result of this research showed that: 1) perceived quality has positive and significant influence on brand trust and 2) brand image has positive and significant influence on brand trust.